Rafting Trip on Oregon's Rogue River - Watkins, Howard::::::::: (1989)
Crew and customers: Jackson Grote and Jan Pearson on far left: Howard Watkins far right and Christine Watkins 3rd from right; Bob Rose shirtless in blue shorts